Covid-19 and Confinement: Effect on Weight Load, Physical Activity and Eating Behavior of Higher Education Students in Southern Morocco - Mohamed Boukrim; Majdouline Obtel; Jalal Kasouati; Abderrahmane Achbani; Rachid Razine (Ubiquity Press, 2021)
Background:Pandemic confinement of COVID-19 may influence dietary behaviors and physical activity, and increases the risk of stress, especially among adolescents. This increases the subsequent risk of degenerative diseases such as obesity, diabetes, cardiovascular disease, etc., which can lead to a higher risk of death. This study aims to evaluate the effect of confinement on the weight load, physical activity and dietary behavior of higher education students during the period of confinement. Methods:Data was collected by an anonymous online questionnaire with 406 students. Physical activity was evaluated with the International Physical Activity Questionnaire. A reference score of the National Nutrition and Health Program (PNNS-GS) was used to determine the dietary habits. Stress appreciation was assessed by using a psychological instrument known as the "Perceived Stress Scale" provided by Mind Garden. Results:More than a quarter of the students were overweight or obese. During the confinement of COVID-19, most of the students suffered from nutritional disorders, only one-third were moderately physically active, and the majority of students were at risk of stress. Multivariate analysis showed that the concept of threat of Stress increases the risk of weight gain at a risk level of 2.4 [95% CI 1.09-5.43], low physical activity increases the risk level to 1.9 [95% CI 1.18-3.04]. However, a balanced diet is protective against the occurrence of weight gain (ORa = 0.30, [95% CI 0.15-0.61]). Conclusion:The study showed that confinement appeared to contribute to weight gain and those students were more sedentary than active with unhealthy eating behaviors. Understanding these behaviors during COVID-19 confinement will help public health authorities implement future policies on recommendations when new pandemics arrive and confinement policies are implemented.